Reestablishment of Plantago bradei (Plantaginaceae), an overlooked narrowly endemic species from Serra do Caparaó, eastern Brazil, and range extension of P. guilleminiana - Hassemer, Gustavo (Phytotaxa, 2017)
This contribution presents morphological and biogeographic evidence for the reestablishment of Plantago bradei (Plantaginaceae), an overlooked narrowly endemic species from the high summits of Serra do Caparaó, a prominent mountainous area in eastern Brazil. Specimens of this taxon were hitherto being identified as P. commersoniana, a morphologically considerably distinct species with a completely different distribution. Plantago bradei can be differentiated from P. commersoniana mainly by the elliptic-lanceolate, coriaceous leaves and the much denser inflorescences. The recognition of P. bradei is also relevant for conservation since it occurs in a single locality and is here assessed as critically endangered. In addition to that, this study presents the first records of P. guilleminiana in Serra do Caparaó, and provides an updated identification key to Plantago in this area.